1983
DOI: 10.3354/meps010277
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, Species Composition and Feeding Impact of Tintinnid Micro-Zooplankton in Central Long Island Sound

Abstract: Abundance and composition of tintinnid and phytoplankton species were followed in central Long Island Sound from August 1979 to October 1980. In all, 28 tintinnid species were observed; the greatest diversity occurred between September and April. Highest tintinnid concentrations occurred in summer, with concentrations of 103 or more individuals I-' observed only when nanophytoplankton concentrations equalled or exceeded 1.3 X 105 cells I-'. Although necessary, the occurrence of small food, alone, was not a suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
3

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(72 citation statements)
references
References 22 publications
4
65
0
3
Order By: Relevance
“…Input of organic nitrogen matter from anthropogenic sources associated with transformation and mobilization large spectrum of food resources, enhance the importance of tintinnids as a key trophic link between the microbial and the metazoan compartments (Fenchel, 1980;Capriulo and Carpenter, 1983;Dolan and Marrasé, 1995;Capriulo et al, 2002;Urrutxurtu, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Input of organic nitrogen matter from anthropogenic sources associated with transformation and mobilization large spectrum of food resources, enhance the importance of tintinnids as a key trophic link between the microbial and the metazoan compartments (Fenchel, 1980;Capriulo and Carpenter, 1983;Dolan and Marrasé, 1995;Capriulo et al, 2002;Urrutxurtu, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Station 3 had a high abundance of tintinnid ciliates. This is not surprising, for this station is just north of the Aleutian Island archipelago, and tintinnids are primarily a coastal microzooplankton group (Beers et al, 1980;Capriulo and Carpenter, 1983;Pierce and Turner, 1993). Fig.…”
Section: Microzooplankton Abundance and Biomassmentioning
confidence: 99%
“…These 2 morphologically diverse subclasses dominate ciliate communities in near-coastal waters. For example, in a 3 yr study in Long Island Sound, Capriulo & Carpenter (1983) and Capriulo et al (2002) reported the presence of 65 species from these groups, based on light microscopy (30 species of tintinnids, 12 other choreotrich species, and 23 oligotrichs).…”
Section: Introductionmentioning
confidence: 99%